A cross-sectional estimation of total factor productivity of livestock-based farming systems in tribal areas of Odisha - Tulika Kumari; A K Chauhan; B S Chandel (Agricultural Economics Research Review, 2024)
The total factor productivity (TFP) of some livestock-based farming systems has been estimated using cross-sectional data and Cobb-Douglas production function. The determinants of TFP in tribal areas of Odisha have also been analysed. The average value of TFP has been observed highest (3.22) for C1 farming system, followed by the C2 (3.19), G1 (3.18), G2 (3.17), P2 (3.14), P1 (3.13) and G3 (3.11) farming systems. It means that the effect of factors other than inputs was more under C1 in comparison to other farming systems. The value of TFP could be increased with a better management of resources and enterprises. The transfer of technology to the farmers could also play a major role in increasing the TFP value of the systems as access to farm extension services has shown a positive and significant effect on TFP. The study has also revealed that the land size has a positive and significant effect on the TFP value. Therefore, collective farming needs to be propagated in this area. For this, farmers should be sensitized through demonstrations and awareness campaigns.